DIFUSI GAGASAN REMUNISIPALISASI TERHADAP PENGELOLAAN AIR DI DKI JAKARTA (Studi Tentang Lembaga Swadaya Masyarakat KRUHA) - Fadhila Firdasari Wijaya (2023)
The background of this thesis discusses the diffusion of remunicipalization ideas carried out by KRUHA towards water management in Jakarta, as well as its interaction with global movements. This idea is an idea adopted from a global movement, so it becomes a challenge for KRUHA. This study uses international norm diffusion theory, with qualitative research methods and case study approaches. Researchers carried out data collection techniques in the form of in-depth interviews and also literature study. The process of data analysis through data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the diffusion of the idea of remunicipalization of kruha is carried out in several ways, such as providing policy advice and building public awareness. In carrying out these efforts KRUHA has also built an international network to facilitate the use of information and multiply support, in which this network is supported by three strategies namely strategic information politics, symbolic politics, and leverage politics. However, Jakarta has different conditions from cities in other countries, so remuneration is not an easy thing to happen. This can be seen from the water infrastructure, secondly from the state model, funding, and also political will.